2009
DOI: 10.1143/jjap.48.081003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phosphorus Implantation on the Activation of Magnesium Doped in GaN

Abstract: The effects of phosphorus implantation on the activation of magnesium doped in GaN at different dopant concentration ratios have been systematically investigated. Hall effect measurements show that P implantation improves the hole concentration, and that this improvement is dependent on P/Mg dopant concentration ratio and annealing conditions. This phenomenon is attributable to the reduction in selfcompensation that results from the formation of deep donors and the enhanced Mg atom activation, which is in reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 13 publications
(15 reference statements)
1
6
0
Order By: Relevance
“…An analogous situation occurs for P-implanted AlGaN:Mg at the surface the ratio P/Mg * 0.1, while for standardized depth of 75%, P/Mg = 2. Thus, these results confirm that an appropriate ratio of P to Mg across the (Al)GaN layers is needed to achieve relatively good p-type conductivity [8,9]. Importantly, a certain amount of Mg in the doped AlGaN structures is a key aspect influencing the electrical parameters.…”
Section: Electrical Characterizationsupporting
confidence: 65%
See 4 more Smart Citations
“…An analogous situation occurs for P-implanted AlGaN:Mg at the surface the ratio P/Mg * 0.1, while for standardized depth of 75%, P/Mg = 2. Thus, these results confirm that an appropriate ratio of P to Mg across the (Al)GaN layers is needed to achieve relatively good p-type conductivity [8,9]. Importantly, a certain amount of Mg in the doped AlGaN structures is a key aspect influencing the electrical parameters.…”
Section: Electrical Characterizationsupporting
confidence: 65%
“…To achieve such effect it is necessary to keep the P/Mg ratio = 0.01-reducing this ratio results in a deterioration of hole concentration (to 6.2 9 10 16 cm -3 for the ratio P/Mg = 0.001). Probably the main reason for such a drastic deterioration of the electrical properties is an inadequate ratio of P/Mg, according to the work of Liu et al [8,9]. The SIMS results showed that for P-implanted GaN:Mg the ratio P/Mg at the surface is about 0.1, but deeper into the sample (* 25%) this ratio significantly changes and is approximately 100.…”
Section: Electrical Characterizationmentioning
confidence: 98%
See 3 more Smart Citations